2019
DOI: 10.1158/0008-5472.can-18-3538
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic Chip Enables Isolation of Exosomes and Establishment of Their Protein Profiles and Associated Signaling Pathways in Ovarian Cancer

Abstract: Because of limits on specificity and purity to allow for indepth protein profiling, a standardized method for exosome isolation has yet to be established. In this study, we describe a novel, in-house microfluidic-based device to isolate exosomes from culture media and patient samples. This technology overcomes contamination issues because sample separation is based on the expression of highly specific surface markers CD63 and EpCAM. Mass spectrometry revealed over 25 exosome proteins that are differentially ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 37 publications
0
71
0
Order By: Relevance
“…Apart from these classic extraction methods, multiple new extraction and detection technologies have been reported in recent years, such as the microfluidic chip 147,148 and a method of integrated extraction and quantitative analysis of exosomal nucleic acids and proteins, 149 with high specificity and intact yield of exosomes, small required sample volume and simple, time-saving operation. Moreover, a novel urine-based EV extraction and enrichment method was established by Woo et al 150 .…”
Section: Progression In Exosome Extraction Methodsmentioning
confidence: 99%
“…Apart from these classic extraction methods, multiple new extraction and detection technologies have been reported in recent years, such as the microfluidic chip 147,148 and a method of integrated extraction and quantitative analysis of exosomal nucleic acids and proteins, 149 with high specificity and intact yield of exosomes, small required sample volume and simple, time-saving operation. Moreover, a novel urine-based EV extraction and enrichment method was established by Woo et al 150 .…”
Section: Progression In Exosome Extraction Methodsmentioning
confidence: 99%
“…To this effect, various malignancies have been studied including melanoma, nasopharyngeal carcinoma, breast cancer, colorectal cancer, and ovarian cancer [97]. Very recently, a microfluidic chip-based liquid biopsy was able to isolate exosomes with detailed protein and signaling pathway profiles in ovarian cancer [99].…”
Section: Exosomes As Pre-metastatic Niche Biomarkers and Therapeuticmentioning
confidence: 99%
“…Reategui et al 86 established a microfluidic platform named (EV)HB-Chip which captured glioblastoma multiformederived characteristic exosomal RNA within 3 hr, contributing to identifying specific genes and subtypes of this disease. Dorayappan et al 87 demonstrated a specific microfluidicbased internal separation device for the establishment of exosomal protein profiles of high-grade serous ovarian cancer (HGSOC) within 20 min, overcoming contamination problems and making new findings for early exosome-based detection. Consequently, the microfluidic chip undoubtedly lays a solid foundation for early diagnosis and prognosis of cancer and it is substantially better than many other existing methods.…”
Section: Microfluidic Techniquesmentioning
confidence: 99%